The Efficacy and Safety of Remimazolam Besylate Combined with Esketamine for Outpatient Colonoscopy: A Prospective, Randomized, Controlled Clinical Trial - Li W; Zhao J; Hao R; Wang S; Chen M; Liu H; Qi L; Hao Z (Dove Medical Press, 2023)
Wei Li, Jun Zhao, Ruiping Hao, Shujuan Wang, Ming Chen, Huijun Liu, Le Qi, Zaijun Hao Department of Anaesthesiology, Ordos Central Hospital, Ordos, Inner Mongolia Autonomous Region, People's Republic of ChinaCorrespondence: Zaijun Hao, Department of Anesthesiology, Ordos Central Hospital, Ordos, Inner Mongolia Autonomous Region, 017000, People's Republic of China, Tel/Fax +8615204778880, Email dengdairy@126.comPurpose: Evaluate the efficacy and safety of remimazolam besylate combined with esketamine for outpatient colonoscopy.Patients and methods: A total of 150 outpatients undergoing colonoscopy were randomized into two groups. A MOAA/S score ≤ 3 was maintained. The primary outcome was the rate of successful colonoscopy completion. Time indicators, hemodynamic parameters, the consumption of lidocaine, esketamine, propofol and remimazolam besylate, MOAA/S scores and bispectral index (BIS) values, the lowest SpO2, body movement, the use of rescue medication, endoscopist and patient satisfaction, recall of the procedure, mini-mental state examination (MMSE), fatigue level and adverse events were recorded.Results: Procedure completion was equivalent between groups (P > 0.05). Both induction and awakening times were significantly shorter in the P group (P < 0.05). There were no significant differences in colonoscopy time and discharge time (P > 0.05). The lowest SpO2 was significantly lower in the P group, while the level of fatigue was higher (P < 0.05). Patient satisfaction was significantly higher in the R group (P < 0.05). Endoscopist satisfaction was significantly higher in the P group (P < 0.05). There were no significant differences in both systolic and diastolic blood pressure between groups except at T5 and T6 (P > 0.05). Both HR and RR were significantly lower in the P group from T3 to T5 (P < 0.05). BIS values were significantly lower in the P group from T3 to T5, while MOAA/S was significantly lower in the P group at T3 and T4 (P < 0.05). Pain on injection was significantly higher in the P group (P < 0.05).Conclusion: Remimazolam besylate has a similar efficacy to propofol when combined with subanesthetic doses of esketamine during outpatient colonoscopy. Remimazolam besylate combined with esketamine resulted in less injection pain and more stable hemodynamics, although it prolonged induction and awakening time.Keywords: remimazolam besylate, propofol, esketamine, colonoscopy